Ensiklopedia Interaktif Alat Musik Tradisional Nusantara Berbasis Website dengan Metode Multimedia Development Life Cycle (MDLC) - Hendrotriyo Priambodo; Indar Sabri; Welly Suryandoko (Universitas Negeri Medan, 2026)
This study developed a website-based interactive encyclopedia to introduce traditional Indonesian musical instruments in arts and culture learning in junior high schools. The research was motivated by the limited collection of traditional musical instruments in schools and the use of learning media that is still one-way and less interactive. The method used is the Multimedia Development Life Cycle (MDLC) with six stages: concept, design, material collecting, assembly, testing, and distribution. Data were collected through school observations, Google Form questionnaires, and in-depth interviews with arts and culture teachers in several junior high schools in Situbondo Regency. The developed product includes educational text, instrument images, authentic audio, real-time virtual instrument features, an AI-based dictionary, and an adaptive quiz game that can be accessed across multiple platforms without installation. The feasibility test results showed an average score of 93.8%, categorized as very feasible. These findings indicate that MDLC-based interactive multimedia is effective, contextual, and relevant for preserving traditional Indonesian music in the digital era.